1999
DOI: 10.1007/bf02976369
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of aromatase activity by flavonoids

Abstract: In searching for potent cancer chemopreventive agents from synthetic or natural products, 28 randomly selected flavonoids were screened for inhibitory effects against partially purified aromatase prepared from human placenta. Over 50% of the flavonoids significantly inhibited aromatase activity, with greatest activity being demonstrated with apigenin (IC50: 0.9 microg/mL), chrysin (IC50: 1.1 microg/mL), and hesperetin (IC50: 1.0 microg/mL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
89
2
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 8 publications
2
89
2
4
Order By: Relevance
“…Prior laboratory research suggests that flavonoids may inhibit breast cancer development by decreasing estrogen production (1,2), inhibiting breast cancer cell proliferation (3), and decreasing reactive oxygen species production (4,5). Several population-based studies (6)(7)(8), including analyses from the Long Island Breast Cancer Study (LIBCSP; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Prior laboratory research suggests that flavonoids may inhibit breast cancer development by decreasing estrogen production (1,2), inhibiting breast cancer cell proliferation (3), and decreasing reactive oxygen species production (4,5). Several population-based studies (6)(7)(8), including analyses from the Long Island Breast Cancer Study (LIBCSP; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Apigenin was found to possess anticarcinogenic, 8) anti-tumor promoter, 9) antioxidative, free radical scavenging and anti-inflammatory activities. 10) Both chrysin and apigenin were found to be potent inhibitors of enzyme aromatase and can protect against breast cancer [11][12][13] and were not mutagenic in the Ames test. [14][15][16] Previous mammalian metabolic studies of chrysin and apigenin in rat showed that they are conjugated at the C-7 hydroxyl group to produce ethereal sulfates and glucuronides, although no structures were provided, and that chrysin is hydroxylated to apigenin.…”
mentioning
confidence: 99%
“…The flavonoid chrysin (5,7-dihydroxyflavone) is present at high levels in honey and propolis (Siess et al, 1996) and in many plant extracts (Williams et al, 1997). In addition to its reported anticarcinogenic (Cardenas et al, 2006), antiviral (Critchfield et al, 1996), antioxidant (Lapidot et al, 2002), and anti-inflammatory (Cho et al, 2004) activities, chrysin has been shown as a potent inhibitor of aromatase (Jeong et al, 1999), an enzyme responsible for the conversion of androstenedione and testosterone into estrone and estradiol, respectively (Meinhardt and Mullis, 2002). As such, chrysin acts as a testosterone-boosting agent and is currently available as dietary supplements used for increasing lean body mass.…”
mentioning
confidence: 99%